Pelatihan Dan Metode Dalam Pelaksanaan Terapi Bekam Kering Pada Penderita Kolesterol Di Klinik Sehat Bersama Kota Makassar - Bachri, Syaiful; Mustarin, Yanti; Suardi, Vivi Adriana; Arnianti, Arnianti; Indra, Indra; Noyumala, Noyumala (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Cholesterol is a type of lipid or fat that is important for body function. Apart from being a source of energy, fat provides the highest number of calories. Cupping is a treatment that consists of four processes, namely suction of the skin and subcutaneous tissue, leaving the glass in a negative pressure position, expelling blood, and precise points. The aim of Community Service (PkM) is to increase cadres' knowledge and provide opportunities for the community to receive cupping therapy to reduce cholesterol levels. The Community Service (PkM) method implemented is training and methods in implementing dry cupping therapy for cholesterol sufferers at the Joint Health Clinic. As a result of this activity, cadres gain knowledge about how to check cholesterol and the community receives cupping therapy. The conclusion is that Community Service (PkM) activities should be sustainable so that they can improve the quality of life of the community.